Testing waterfowl hunters’ waterfowl identification skills - Ahlers, Adam A.; Miller, Craig A. (Wildfowl, 2019)
Waterfowl management in North America is partially informed by hunter harvest data, which includes the number and sex of each species harvested. Self-reporting harvest via online surveys or paper forms is common for many agencies and at wildlife management areas. For these data to be useful to managers, however, it is critical that self-reported harvest data are precise and accurate. If this assumption is violated, harvest data may be biased and subsequent management efforts misinformed. We surveyed waterfowl hunters (n = 149) in Kansas, USA, immediately after the regular waterfowl hunting season in autumn–winter 2017/2018 to assess their ability to identify waterfowl to species and sex. In particular, participants attending events focused on waterfowl hunting and wetland conservation were asked to complete a survey that tested their ability to identify Northern Pintail Anas acuta, Lesser Scaup Aythya affinis, Canvasback Aythya valisineria and Redhead Aythya americana from colour photographs of breeding-plumage waterbirds commonly encountered in North America’s Central Flyway. Respondents’ average number of days spent hunting waterfowl during the 2017/2018 Kansas waterfowl season was 22 days – almost six times greater than the average Kansas waterfowl hunter during the same season. Seventy-nine percent of respondents misidentified at least one photograph. The number of days that an individual hunted during the 2017/2018 waterfowl season was generally a good predictor of successful identification. Participants misidentified female Lesser Scaup and Redhead more than other species and sex. Given that our survey included avid waterfowl hunters and high-definition photographs of waterfowl in breeding plumage, our results likely underestimate false identifications and suggest there may be a bias in self-reported waterfowl harvest data. We propose that self-reporting mediums for waterfowl harvest (both online and on paper forms) also include colour photographs of species that could potentially be harvested within the area of reporting.